How to sell value - demystified : a practical guide for communications agencies - Manners, Crispin (PRCA professional, 2023)
The latest research from the Public Relations and Communications Association (PRCA) demonstrates that 83% of agencies do not sell by value. This represents a significant threat to their future, especially during recessionary times, as it means there is unlikely to be the proof needed to sustain the budgets that clients currently allocate for their services. If agencies don't start proving the business value of what they do, the consequences are likely to be a significant loss of income, with a dire impact on the future potential of the agency. In How to Sell Value - Demystified: A Practical Guide for Communications Agencies, acclaimed PR guru Crispin Manners explains how agencies can move quickly to a value-based, rather than time-based, agency model. The author addresses key issues such as: The power of a branded methodology that builds trust and confidence and sets client expectations correctly The tools that bring a branded method to life and give the team ways to reinforce it Examples of premium priced services that break the time-based pricing model How to set a value-based price The importance of client data in proving value and driving effective evaluation. This practical guide clearly outlines a route to a more profitable and fulfilling agency, one where everyone involved gets a true sense of achievement because of the value they know they deliver to their clients.